Defending God : biblical responses to the problem of evil - Crenshaw, James L. (Oxford University Press, 2005)
What motivates the centuries old human endeavour to impose moral standards of behaviour on the gods? James Crenshaw offers a synthesis of his ideas on the subject of theodicy & the struggle to absolve the deity of responsibility for injustice.